(3GdWQjb Gdi GMJQGa dZI (Bjava /s - (3YRH, YRH eMeOs; (3eGLO, eUWai s ((3GdbGgQI(B: s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B, s, 2002)
(3CSGSjGJ GdHjGfGJ aj dZI GdLGaG(B- (3GdeUahaGJ hLed GdJMce aj eSGQ GdHQfGeL hLed GdJcQGQ(B- (3eaGgje GdHQeLI HGdGgOGa(B- (3bhGYO JhGUd GdaUGFd(B- (3COhGJ GdecJHI(B- (3eOjQ GdJNWjW heYGdLI GdMOK(B- (3GSJKfGAGJ heYGdLJgG(B- (3GdJOab(B- (3GdegGe(B- (3GdTHcGJ(B- (3dZI GdESJYdGeGJ(B- (3bhGYO GdHjGfGJ aj GdLGaG(B- (3JWHjbGJ YedjI(B.s
Keywords: (3GdEYdGe GdCdjs; (3GdHQeLjGJs; (3GdMGShHs; (3dZGJ GdHQeLI(B- (3LGaGs